2020
DOI: 10.3762/bjnano.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization vs decoupling: influence of an h-BN interlayer on the physical properties of a lander-type molecule on Ni(111)

Abstract: 2D materials such as hexagonal boron nitride (h-BN) are widely used to decouple organic molecules from metal substrates. Nevertheless, there are also indications in the literature for a significant hybridization, which results in a perturbation of the intrinsic molecular properties. In this work we study the electronic and optical properties as well as the lateral structure of tetraphenyldibenzoperiflanthene (DBP) on Ni(111) with and without an atomically thin h-BN interlayer to investigate its possible decoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…21). To provide direct evidence of the single-crystalline quality of the graphene directly grown on Al2O3, we applied distortion corrected low energy electron diffraction (LEED) [33][34][35] . The LEED patterns obtained (Supplementary Fig.…”
Section: Growth Of Inch-sized Single-crystal Graphene Film On a Al2o3...mentioning
confidence: 99%
See 1 more Smart Citation
“…21). To provide direct evidence of the single-crystalline quality of the graphene directly grown on Al2O3, we applied distortion corrected low energy electron diffraction (LEED) [33][34][35] . The LEED patterns obtained (Supplementary Fig.…”
Section: Growth Of Inch-sized Single-crystal Graphene Film On a Al2o3...mentioning
confidence: 99%
“…In order to prevent charging of the insulating substrate, a double multi-channel plate (MCP) LEED (MCP2-LEED, OCI Vacuum Microengineering) was used, and the graphene layer was contacted from the top by use of a molybdenum mask sparing a circular measurement area. Further, we applied distortion correction to the LEED images, as described in the literature 33,34 , by applying the software LEEDLab and LEEDCal 35 . Depth profiling experiments were performed on a dynamic secondary ion mass spectrometer (D-SIMS, Hiden Analytical, UK) operated under ultra-high vacuum conditions, typically 10 -9 torr.…”
Section: Growth Of Aligned Mos2 Domains On Direct-grown Graphenementioning
confidence: 99%
“…2 These devices are commonly constructed using thin film technology, therefore it is important to understand the influence a surface can have on DBP if the molecule is deposited on it. A metal surface can change the electronic structure of DBP, 3 but an additional layer of a two-dimensional material or a thin film of an insulator can be used to shield DBP from interacting with the electrode, thus electronically decoupling the two materials. 3 For example, DBP was reported not to hybridize with a graphite surface.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a buffer layer interposed between the substrate and the molecular film can improve the crystallinity of the latter and reduce the electronic coupling with the support [22]. The buffer layer can either be a thin oxide film [23][24][25][26] or a single layer of 2D material, such as graphene [27,28], hexago-nal boron nitride [29][30][31] and MoS 2 [32,33]. Moreover, an organic layer inserted between the substrate and the overlayer has been shown to be effective in improving the order of the molecular film [34,35] or restoring its original electronic structure [36][37][38].…”
Section: Introductionmentioning
confidence: 99%